Repercussões da jornada de trinta horas: o trabalho de assistentes sociais em entidades conveniadas no município de Diadema-SP - Monteiro, Claudia Lima (2021)
The general objective of this thesis was to analyze the working hours of thirty hours per week in the daily professional life of social workers working in entities associated with the Municipality of Diadema (PMD). The theoretical and methodological framework was marxist social theory, comprising the categories of movement, contradiction, historicity, and totality as foundations for the study of the object. The bibliographic references were based on authors from the areas of Social Work, Sociology of Work and Health of the Worker for the theoretical foundation on work day, intensification, precariousness and outsourcing of work and its expressions in the daily work of social workers. The documentary research consisted of consultations with legislation and official documents, especially the Transparency Portal, for the identification of agreements established by the LDC with entities for the execution of public policies. The field research, of qualitative nature, was carried out with 14 social workers inserted in different entities associated with the PMD, through questionnaires and interviews. As a result of the splitsite doctoral program, the thesis also included bibliographic research on the working day in Portugal and field study, through an interview with the director of the Union of Public Administration Workers and Public Entities (SINTAP). The results of the research, in Brazil, revealed the existence of PMD agreements with entities in the areas of Culture, Sport and Leisure, Health, Education and Social Assistance, with exponential growth in these last two areas. Predominantly, social workers were hired by the entities with the correct nomenclature, that is, for the position of social workers, for thirty hours per week and with registration in portfolio. A large volume and density of the activities developed, extra demands due to the agreements, deficit of professionals and intensification of work rhythms were identified, reflecting the length of the working day with the performance of bank hours or overtime compensation and the flexibilization of some working hours. In relation to the statutory social workers of the LDCs, the interviewees reported being in more adverse working conditions, considering the difference in salary and insecurity in relation to the maintenance of employment. Even in view of the difficulties encountered for the delimitation of the thirty hours per week, the interviewees unanimously valued this achievement and recognized its importance for the recovery of physical and mental health, in view of the daily performance with the expressions of the social issue